Statistics for the behavioral sciences : analysis and application for the public sector - Gravetter, Frederick J.; Wallnau, Larry B. (Belmont, MO : Wadsworth, 2006)
The best-selling introduction to statistics for students in the behavioral and social sciences, the Seventh Edition of STATISTICS FOR THE BEHAVIORAL SCIENCES continues to offer students straightforward instruction, accuracy, built-in learning aids, and real-world examples. Authors Frederick Gravetter and Larry Wallnau help students understand statistical procedures through a conceptual context that explains why the procedure was developed and when it should be used. The authors offer students numerous opportunities to practice statistical techniques through learning checks, examples, demonstrations, and problems. Instructors value the unparalleled ancillary package that accompanies this book, now including JoinInTM on TurningPoint?content for Personal Response System "clickers."
Introduction to statistics -- Frequency distributions -- Central tendency -- Variability -- z-Scores: location of scores and standardized distributions -- Probability -- Probability and samples -- Introduction to hypothesis testing -- Introduction to the t statistic -- The t test for two independent samples -- The t test for two related samples -- Estimation -- Introduction to the analysis of variance -- Repeated-measures analysis of variance (ANOVA) -- Two-factor analysis of variance (independent measures) -- Correlation -- Introduction to regression -- The chisquare statistic: tests for goodness of fit and independence -- The binomial test -- Statistical techniques for ordinal data: Mann-Whitney, Wilcoxon, Kruskal Wallis, and Friedman tests -- Appendix A. Basic -- mathematics review -- Appendix B. Statistical tables -- Appendix C. Solutions for odd-numbered problems -- Appendix D. General instructions for using SPSS -- Statistics organizer.
Includes bibliographical references (p. 750-752) and index.
1
Keywords: Psychology -- Statistical methods; ducational statistics